Pemphigus foliaceus in a patient with psoriasis vulgaris - Marańska, Dagmara; Łoza, Katarzyna; Gręda, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction. Pemphigus foliaceus is a rare variety of pemphigus. It is an autoimmune skin disorder characterized by the loss of intracellular adhesion of keratinocytes in the upper part of the epidermis, resulting in the formation of superficial blisters. Pemphigus may be provoked by drugs, UV light, burns and diet. Coexistence of bullous pemphigoid and psoriasis is well known, whereas appearance of pemphigus in patients with psoriasis is rarely described. Objective. Presentation of a patient with psoriasis vulgaris in whom pemphigus foliaceus provoked by UVB 311 developed. Case report. The patient, a 52-year-old male suffering from psoriasis vulgaris for five years, was hospitalized at the Department of Adult Dermatology. In the course of phototherapy with UVB 311, lesions clinically, histopathologically and immunopathologically characteristic for pemphigus foliaceus appeared. He was treated with prednisolone in a dose of 0.8 mg/kg/day and azathioprine (150 mg/day). Due to the severe side-effects – pneumonia and haemorrhagic stroke – azathioprine was discontinued and the dose of prednisolone was diminished. In spite of the lowered dose of corticosteroids healing of skin lesions and decrease of pemphigus antibodies titre were observed. The patient, in good general and skin condition, treated with 30 mg of prednisolone every second day, is under further medical observation. Conclusions. We present a patient with pemphigus foliaceus, most probably provoked by UVB 311. The case illustrates the therapeutic difficulties observed in rare cases of coexistence of pemphigus foliaceus with psoriasis vulgaris.